Flame-retardant polyamide resin composition and molded article

By adding aliphatic polyamide, semi-aromatic polyamide and surfactant to the flame retardant polyamide resin, combined with a method of uniformly dispersing melamine cyanurate, the problem of large size changes in flame retardant polyamide resin during water absorption is solved, and both flame retardant and mechanical strength are achieved.

CN119875360APending Publication Date: 2025-04-25ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411449808.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-24
Filing Date
2024-10-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing flame retardant polyamide resins have large size changes when absorbing water, making it difficult to take into account both mechanical strength and flame retardant properties, especially in the flame retardation of the V-0 level of UL94.

Method used

The flame retardant polyamide resin composition containing aliphatic polyamide, semiaromatic polyamide and surfactant is used to ensure uniform dispersion of melamine cyanurate and improve flame retardancy and mechanical strength by adjusting the composition component ratio and the use of surfactant.

Benefits of technology

The polyamide resin composition and molded body with low water absorption, small dimensional change rate during water absorption, excellent flame retardancy and mechanical strength are realized, and are suitable for components requiring high mechanical characteristics and flame retardancy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a flame-retardant polyamide resin composition and a molded body. The purpose of the present invention is to provide: a polyamide resin composition having low water absorbency, a small dimensional change rate when absorbing water, and excellent flame retardancy and mechanical strength; and a molded article obtained by molding the polyamide resin composition. A flame-retardant polyamide resin composition which contains (A) a polyamide resin that contains (a-1) an aliphatic polyamide and (a-2) a semi-aromatic polyamide, (B) a melamine cyanurate, and (C) a surfactant, and which is characterized in that when the flame-retardant polyamide resin composition is taken as 100% by mass, the content of the melamine cyanurate in the polyamide resin (A) is less than or equal to 1% by mass, and the content of the melamine cyanurate in the semi-aromatic polyamide (A) is less than or equal to 1% by mass. The flame-retardant polyamide resin composition contains 55 to 95 mass% of (a-1) an aliphatic polyamide, 1 to 30 mass% of (a-2) a semi-aromatic polyamide, 4 to 15 mass% of (B) a melamine cyanurate, and 0.01 to 5.0 mass% of (C) a surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a flame-retardant polyamide resin composition and a molded product. Background Art

[0002] Polyamide resin has excellent properties such as mechanical properties and molding processability, so it has been widely used in various parts such as automobile parts, electronic and electrical parts, and industrial machinery parts. In particular, due to its excellent toughness, it is used in electrical and electronic products such as connectors and clips. In many cases, these products require flame retardancy.

[0003] As a method for imparting flame retardancy to polyamide resins, a method of mixing a halogen-containing organic compound as a flame retardant and a metal oxide such as an antimony compound as a flame retardant aid with a resin is generally used. However, in particular, from an environmental point of view, it is desirable to use a non-halogen-containing flame retardant. In addition, a resin composition with a halogen-containing flame retardant has problems such as reduced electrical properties such as tracking resistance. Therefore, in recent years, it is strongly desired to use these halogen-free flame retardants.

[0004] As a representative example of such flame-retardant polyamide resins, flame-retardant polyamide materials containing melamine cyanurate are mentioned, for example, connectors and clips used in the electrical and electronic fields (Patent Document 1). In addition, a polyamide resin composition containing a specific triester of phosphoric acid, a higher fatty acid metal salt and a polyol is proposed in Patent Document 2. In addition, a polyamide resin composition having excellent hinge properties and containing aliphatic polyamide and semi-aromatic polyamide is proposed in Patent Document 3.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-070808

[0008] Patent Document 2: Japanese Patent Application Publication No. 2008-007614

[0009] Patent Document 3: Japanese Patent Application Publication No. 2000-26721 Summary of the invention

[0010] Problems to be solved by the invention

[0011] Among the flame-retardant polyamide resins using melamine cyanurate, polyamide 66 and polyamide 6 are representative, but these resins have large dimensional changes when absorbing water and are generally not suitable for situations where dimensional accuracy when absorbing water is required. In addition, long-chain polyamides represented by polyamide 610 and polyamide 612 have relatively low water absorption and small dimensional change rates when absorbing water. However, flame retardancy based on the V-0 level of UL94 is difficult and requires a large amount of flame retardants, so it is difficult to have both mechanical strength and flame retardancy.

[0012] The present invention has been made in view of the above circumstances, and an object thereof is to provide a polyamide resin composition having low water absorption, a small dimensional change rate when absorbing water, and excellent flame retardancy and mechanical strength, and a molded product obtained by molding the polyamide resin composition.

[0013] Means used to solve problems

[0014] That is, the present invention is as follows.

[0015] (1) A flame-retardant polyamide resin composition comprising (A) a polyamide resin, (B) melamine cyanurate, and (C) a surfactant, wherein the (A) polyamide resin comprises (a-1) an aliphatic polyamide and (a-2) a semi-aromatic polyamide, wherein:

[0016] When the flame-retardant polyamide resin composition is set to 100 mass %, the flame-retardant polyamide resin composition includes: 55 mass % to 95 mass % of the (a-1) aliphatic polyamide, 1 mass % to 30 mass % of the (a-2) semi-aromatic polyamide, 4 mass % to 15 mass % of the (B) melamine cyanurate, and 0.01 mass % to 5.0 mass % of the (C) surfactant.

[0017] (2) The flame-retardant polyamide resin composition according to (1), wherein when a slice of the flame-retardant polyamide resin composition is photographed at a magnification of 100 times using a digital microscope, when the total amount (number) of the (B) melamine cyanurate particles in an image of 800 μm×800 μm square is set to 100%, the area of ​​the particles is 100 μm in the image of 800 μm×800 μm square. 2 The ratio of the (B) melamine cyanurate in the form of the above particles is less than 10%.

[0018] (3) The flame-retardant polyamide resin composition according to (1) or (2), wherein when a slice of the flame-retardant polyamide resin composition is photographed at a magnification of 100 times using a digital microscope, when the total amount (number) of the melamine cyanurate particles (B) in an image of 800 μm×800 μm square is set to 100%, the area of ​​the particles is 10 μm in the image of 800 μm×800 μm square. 2 The ratio of the (B) melamine cyanurate in the form of particles is 10% or more and less than 50%.

[0019] (4) The flame-retardant polyamide resin composition according to any one of (1) to (3), wherein the (B) melamine cyanurate is melamine cyanurate surface-modified with the (C) surfactant.

[0020] (5) A molded product obtained by molding the flame-retardant polyamide resin composition according to any one of (1) to (4).

[0021] Effects of the Invention

[0022] According to the present invention, there can be provided a polyamide resin composition having low water absorption, a small dimensional change rate when absorbing water, and excellent flame retardancy and mechanical strength, and a molded product obtained by molding the polyamide resin composition. DETAILED DESCRIPTION

[0023] Hereinafter, a mode for implementing the present invention (hereinafter referred to as “this embodiment”) will be described in detail. It should be noted that the present invention is not limited to the following embodiment, and can be implemented with various modifications within the scope of the gist thereof.

[0024] In this specification, "polyamide resin" refers to a polymer compound having a "-CO-NH-" (amide) bond in the main chain.

[0025] <Flame-retardant polyamide resin composition>

[0026] The flame-retardant polyamide resin composition of the present embodiment (hereinafter also simply referred to as “polyamide resin composition”) contains (A) a polyamide resin, (B) melamine cyanurate, and (C) a surfactant, and may optionally contain additives described below.

[0027] Hereinafter, each constituent component constituting the flame-retardant polyamide resin composition according to the present embodiment will be described in detail.

[0028] <(A) Polyamide resin>

[0029] The (A) polyamide resin contained in the flame-retardant polyamide resin composition of the present embodiment includes (a-1) aliphatic polyamide and (a-2) semi-aromatic polyamide. The (A) polyamide resin may optionally include polyamides other than the (a-1) aliphatic polyamide and the (a-2) semi-aromatic polyamide.

[0030] [(a-1) Aliphatic polyamide]

[0031] The (a-1) aliphatic polyamide of the present embodiment is preferably a homopolymer or copolymer of a polyamide obtained by polycondensation of a lactam having three or more rings, a polymerizable (polycondensed) ω-aminocarboxylic acid, or an aliphatic dicarboxylic acid and an aliphatic diamine. That is, the (a-1) aliphatic polyamide preferably contains one or more selected from the group consisting of a lactam unit and an aminocarboxylic acid unit and / or contains an aliphatic dicarboxylic acid unit and an aliphatic diamine unit.

[0032] Specifically, there can be mentioned: polymers obtained by polycondensing lactams such as ε-caprolactam, enantholactam, α-pyrrolidone, and α-piperidone, and ω-aminocarboxylic acids such as aminocaproic acid, 7-aminoheptanoic acid, 11-aminoundecanoic acid, and 9-aminononanoic acid; polymers obtained by polycondensing tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, octamethylenediamine, nonamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4 (or 2,4,4)-trimethylhexamethylenediamine; Polymers obtained by polycondensation of an aliphatic diamine such as methyldiamine and bis(4,4'-aminocyclohexyl)methane with an aliphatic dicarboxylic acid such as adipic acid, succinic acid, dodecanedioic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, hexadecanedioic acid, hexadecenedioic acid, eicosanedioic acid, eicosadienedioic acid, diglycolic acid, 2,2,4-trimethyladipic acid, 1,4-cyclohexanedicarboxylic acid, or copolymers thereof.

[0033] As the aliphatic diamine, hexamethylenediamine is preferred. The aliphatic diamine may be used alone or in combination of two or more.

[0034] The aliphatic dicarboxylic acid is preferably an α,ω-straight-chain aliphatic dicarboxylic acid, and more preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 6 to 12 carbon atoms. The aliphatic dicarboxylic acid may be used alone or in combination of two or more.

[0035] Specific examples of the (a-1) aliphatic polyamide include polyamide 4, polyamide 6, polyamide 7, polyamide 8, polyamide 11, polyamide 12, polyamide 66, polyamide 69, polyamide 610, polyamide 611, polyamide 612, polyamide 66 / 6 copolymer, etc. Preferred are polyamide 66, polyamide 66 / 6 copolymer, polyamide 610, polyamide 612, polyamide 11, and polyamide 12, and more preferred are aliphatic polyamides having an average number of carbon atoms per nitrogen atom per monomer unit of 8 or more.

[0036] The average number of carbon atoms per monomer unit in the (a-1) aliphatic polyamide is calculated by dividing the total number of carbon atoms in the monomers used by the number of monomers used.

[0037] Examples of the (a-1) aliphatic polyamide having an average number of carbon atoms per monomer unit relative to nitrogen atoms per monomer unit of 8 or more include polyamide 610, polyamide 612, polyundecalactam (polyamide 11), polyamide 12, and polyamide copolymers obtained by copolymerizing two or more of these polyamides.

[0038] (a-1) The aliphatic polyamide may be used alone or in combination of two or more.

[0039] Among the above, polyamide 610 and polyamide 612 are particularly preferred because they have a good balance between low water absorption and flame retardancy.

[0040] From the viewpoint of moldability and mechanical properties, the content of the (a-1) aliphatic polyamide in the polyamide resin composition of the present embodiment is 55% by mass or more, preferably 70% by mass or more, and more preferably 80% by mass or more, relative to the total mass 100% by mass of the polyamide resin composition. In addition, from the viewpoint of flame retardancy, the content of the (a-1) aliphatic polyamide in the polyamide resin composition is 95% by mass or less, preferably 90% by mass or less, and more preferably 85% by mass or less.

[0041] From the viewpoint of fluidity and mechanical properties, the weight average molecular weight Mw of the aliphatic polyamide (a-1) is preferably 20,000 to 50,000, more preferably 25,000 to 45,000, and even more preferably 28,000 to 40,000.

[0042] From the viewpoint of fluidity, the molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of the (a-1) aliphatic polyamide is preferably 1.0 to 3.0, more preferably 1.5 to 2.5, and even more preferably 1.8 to 2.4.

[0043] In addition, the weight average molecular weight Mw and the number average molecular weight Mn of the (a-1) aliphatic polyamide can be measured using gel permeation chromatography (GPC).

[0044] [(a-2) Semi-aromatic polyamide]

[0045] The (a-2) semi-aromatic polyamide in the present embodiment is preferably a polyamide obtained by polycondensation of a dicarboxylic acid, one of which is aliphatic and the other is aromatic, and a diamine. That is, the (a-2) semi-aromatic polyamide preferably contains an aliphatic dicarboxylic acid unit and an aromatic diamine unit, or contains an aromatic dicarboxylic acid unit and an aliphatic diamine unit.

[0046] Examples of the aliphatic dicarboxylic acid and the aliphatic diamine include the same ones as those exemplified above regarding the aliphatic polyamide (a-1). The aliphatic dicarboxylic acid and the aliphatic diamine may be used alone or in combination of two or more.

[0047] Examples of aromatic dicarboxylic acids include terephthalic acid and isophthalic acid, and examples of aromatic diamines include meta-xylylenediamine, etc. The aromatic dicarboxylic acids and aromatic diamines may be used alone or in combination of two or more.

[0048] Examples of the (a-2) semi-aromatic polyamide include polyamide 6T, polyamide MXD6, polyamide 6I, and polyamide 6I / 6T.

[0049] (a-2) The semi-aromatic polyamide may be used alone or in combination of two or more.

[0050] The (a-2) semi-aromatic polyamide contained in the polyamide resin composition of the present embodiment is preferably a polyamide containing dicarboxylic acid units and diamine units, wherein the dicarboxylic acid units contain 75 mol % or more of isophthalic acid units based on all the dicarboxylic acid units of the (a-2) semi-aromatic polyamide, and the diamine units contain 50 mol % or more of diamine units having 4 to 10 carbon atoms based on all the diamine units of the (a-2) semi-aromatic polyamide.

[0051] In this case, the total content of the isophthalic acid units and the diamine units having 4 to 10 carbon atoms in the (a-2) semi-aromatic polyamide is preferably 80 mol % to 100 mol %, more preferably 90 mol % to 100 mol %, and even more preferably 100 mol %, relative to all the structural units of the (a-2) semi-aromatic polyamide.

[0052] From the viewpoint of dimensional stability and flame retardancy during water absorption, the content of the (a-2) semi-aromatic polyamide in the polyamide resin composition of the present embodiment is 1% by mass or more and 30% by mass or less, preferably 5% by mass or more and 25% by mass or less, and more preferably 5% by mass or more and 15% by mass or less, relative to 100% by mass of the total mass of the polyamide resin composition.

[0053] From the viewpoint of mechanical properties and flame retardancy, the difference between the weight average molecular weight Mw of the (a-2) semi-aromatic polyamide and the weight average molecular weight Mw of the (a-1) aliphatic polyamide is preferably within ±30,000, more preferably within ±25,000, and even more preferably within ±20,000.

[0054] From the viewpoint of moldability and appearance, the molecular weight distribution (weight average molecular weight Mw / number average molecular weight Mn) of the (a-2) semi-aromatic polyamide is preferably 1.0 to 3.0, more preferably 1.5 to 2.7, and even more preferably 2.0 to 2.5.

[0055] In addition, the weight average molecular weight Mw and the number average molecular weight Mn of the (a-2) semi-aromatic polyamide can be measured using GPC.

[0056] The 96% sulfuric acid relative viscosity ηr of the polyamide resin (A) is preferably 1.9 to 2.8, more preferably 2.0 to 2.7, and even more preferably 2.1 to 2.6. When the 96% sulfuric acid relative viscosity ηr of the polyamide resin (A) is within the above range, the fluidity and mechanical properties of the polyamide resin composition tend to be more excellent.

[0057] In addition, the 98% sulfuric acid relative viscosity ηr is a value measured according to JIS K6920.

[0058] <(A) Method for producing polyamide resin>

[0059] In the production of (A) the polyamide resin (including the case where the polyamide resin is a polyamide copolymer, (a-1) the aliphatic polyamide and (a-2) the semi-aromatic polyamide), a predetermined catalyst can be used.

[0060] The catalyst is not particularly limited as long as it is a known catalyst for synthesizing polyamide resins, and examples thereof include phosphoric acid, phosphorous acid, hypophosphorous acid, orthophosphorous acid, pyrophosphorous acid, phenylphosphinic acid, phenylphosphonic acid, 2-methoxyphenylphosphonic acid, 2-(2'-pyridyl)ethylphosphonic acid, and metal salts thereof. Examples of the metal of the metal salt include, but are not limited to, metal salts or ammonium salts of potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, antimony, and the like.

[0061] Furthermore, as the catalyst, phosphoric acid esters such as ethyl ester, isopropyl ester, butyl ester, hexyl ester, decyl ester, isodecyl ester, octadecyl ester, stearyl ester, and phenyl ester can also be used.

[0062] [Methods for producing (a-1) aliphatic polyamide and (a-2) semi-aromatic polyamide]

[0063] When the polyamide (A) contained in the polyamide resin composition of the present embodiment is produced by polycondensing a dicarboxylic acid and a diamine, the amount of the dicarboxylic acid added and the amount of the diamine added are preferably about the same molar amount. Regarding the molar ratio, taking into account the amount of diamine released to the outside of the reaction system during the polymerization reaction, the molar amount of all diamines relative to the molar amount of all dicarboxylic acids is preferably 0.9 to 1.2, more preferably 0.95 to 1.1, and even more preferably 0.98 to 1.05.

[0064] (A) The method for producing polyamide includes, for example, the following polymerization step (1) or (2), but is not limited thereto.

[0065] (1) A step of polymerizing a combination of a dicarboxylic acid constituting a dicarboxylic acid unit and a diamine constituting a diamine unit to obtain a polymer.

[0066] (2) A step of polymerizing one or more selected from the group consisting of lactam constituting a lactam unit and aminocarboxylic acid constituting an aminocarboxylic acid unit to obtain a polymer.

[0067] In addition, the method for producing the polyamide resin (A) preferably further comprises a step of increasing the degree of polymerization of the polyamide after the polymerization step. In addition, an end-capping step of capping the ends of the obtained polymer with an end-capping agent may be included after the polymerization step and the increase step as required.

[0068] (A) As a specific method for producing the polyamide resin, for example, various methods as exemplified in the following 1) to 4) are exemplified.

[0069] 1) A method in which an aqueous solution or aqueous suspension of at least one selected from the group consisting of a dicarboxylic acid-diamine salt, a mixture of a dicarboxylic acid and a diamine, a lactam, and an aminocarboxylic acid is heated to polymerize while maintaining the molten state (hereinafter sometimes referred to as "hot melt polymerization method").

[0070] 2) A method of increasing the degree of polymerization of a polyamide obtained by a hot melt polymerization method at a temperature below the melting point while maintaining the polyamide in a solid state.

[0071] 3) A method of polymerizing one or more selected from the group consisting of a dicarboxylic acid-diamine salt, a mixture of a dicarboxylic acid and a diamine, a lactam, and an aminocarboxylic acid while maintaining a solid state.

[0072] 4) A method of polymerizing using a dicarboxylic acid halide component and a diamine component that are equivalent to a dicarboxylic acid.

[0073] Among them, as a specific method for producing the polyamide resin (A), a method for producing the polyamide resin by hot melt polymerization is preferred. In addition, when producing the polyamide resin (A) by hot melt polymerization, it is preferred to keep the molten state until the polymerization is completed. In order to keep the molten state, it is necessary to produce under polymerization conditions suitable for the polyamide resin. As polymerization conditions, for example, the conditions shown below can be cited. First, the polymerization pressure in the hot melt polymerization method is controlled to 14 kg / cm 2 Above and 25kg / cm 2 Next, the pressure in the tank was reduced over 30 minutes until it reached atmospheric pressure (gauge pressure = 0 kg / cm 2 ).

[0074] In the method for producing the polyamide resin (A), the polymerization method is not particularly limited, and may be a batch method or a continuous method.

[0075] The polymerization apparatus used for producing the (A) polyamide resin is not particularly limited, and a known apparatus can be used. Specific examples of the polymerization apparatus include autoclave reactors, drum reactors, extruder reactors (kneaders, etc.), and the like.

[0076] Hereinafter, as a method for producing the polyamide resin (A), a method for producing the polyamide resin (A) by a batch hot melt polymerization method will be specifically described, but the method for producing the polyamide resin (A) is not limited thereto.

[0077] First, an aqueous solution containing about 40% by mass or more and about 60% by mass or less of a raw material component of (A) a polyamide resin (at least one selected from the group consisting of a combination of a dicarboxylic acid and a diamine, a lactam, and an aminocarboxylic acid) is prepared. Next, the aqueous solution is concentrated to about 65% by mass or more and about 90% by mass or less in a concentration tank operated at a temperature of 110° C. to 180° C. and a pressure of about 0.035 MPa to about 0.6 MPa (gauge pressure) to obtain a concentrated solution.

[0078] Next, the obtained concentrated solution was transferred to an autoclave, and heating was continued until the pressure in the autoclave reached about 1.2 MPa or more and about 2.2 MPa or less (gauge pressure).

[0079] Next, in the autoclave, the pressure is maintained at about 1.2 MPa or more and about 2.2 MPa or less (gauge pressure) while at least one of water and gas components is extracted. Next, when the temperature reaches about 220°C or more and about 260°C or less, the pressure is reduced to atmospheric pressure (gauge pressure is 0 MPa). After the pressure in the autoclave is reduced to atmospheric pressure, the pressure is reduced as needed, thereby effectively removing water generated as a by-product.

[0080] Next, the autoclave is pressurized with an inert gas such as nitrogen, and the polyamide melt is extruded from the autoclave in the form of strands. The extruded strands are cooled and cut to obtain pellets of the (A) polyamide resin.

[0081] <(B) Melamine cyanurate>

[0082] (B) Melamine cyanurate is the equimolar reaction product of melamine and cyanuric acid.

[0083] (B) Melamine cyanurate may contain 0.001% by mass or more and 0.30% by mass or less of unreacted melamine or cyanuric acid relative to the total mass of (B) melamine cyanurate. Such melamine cyanurate is commercially available, and industrially available melamine cyanurate can be used as appropriate.

[0084] Median particle size (D) of (B) melamine cyanurate before mixing with (A) polyamide resin 50 ) is not particularly limited, but from the viewpoint of the dispersibility of melamine cyanurate (B), it is preferably 1 μm or more and 20 μm or less, and more preferably 1.5 μm or more and 15 μm or less. When the median particle size of melamine cyanurate (B) is greater than or equal to the above lower limit, handling becomes easier, and the deterioration of the cohesion of melamine cyanurate (B) can be further suppressed. In addition, when the median particle size of melamine cyanurate (B) is less than or equal to the above upper limit, the balance between dispersibility and handling in the polyamide resin composition is more excellent.

[0085] Here, the median particle size (D 50 ) As defined in JIS Z8901, it refers to the particle size when the mass of particles larger than a certain particle size accounts for 50% by mass of the mass of all particles in the particle size distribution, and can be measured by a laser diffraction scattering method. Specifically, it can be measured as follows: by using the laser diffraction scattering method, a graph is drawn with the particle size as the horizontal axis and the frequency (mass) as the vertical axis, and the particle size is measured as the particle size when the cumulative mass reaches 50% by mass when the sum of the cumulative mass of the frequency is set to 100% by mass.

[0086] From the viewpoint of flame retardancy and toughness, the content of (B) melamine cyanurate is 4 to 15 mass %, preferably 4.5 to 12 mass %, more preferably 5 to 8 mass %, based on 100 mass % of the total mass of the polyamide resin composition.

[0087] <(C) Surfactant>

[0088] (C) The surfactant may be any type as long as it can be used to disperse (B) melamine cyanurate in (A) polyamide resin, but fatty acid esters of polyols and polyalkylene polyols are preferred.

[0089] Examples of the polyol include polyalkylene polyols such as polyethylene glycol, polypropylene glycol, and polybutylene glycol.

[0090] In addition, examples of fatty acid esters of polyalkylene polyols include esters of polyalkylene polyols such as polyethylene glycol, polypropylene glycol, and polybutylene glycol with aliphatic carboxylic acids such as capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, cerotic acid, montanic acid, melissic acid, oleic acid, and erucic acid, or derivatives thereof, which are easily available industrially.

[0091] Among them, from the viewpoint of dispersibility of (B) melamine cyanurate, polyethylene glycol or a fatty acid ester of polyethylene glycol is preferred, and a higher fatty acid (having 12 or more carbon atoms) ester of polyethylene glycol or a derivative thereof is more preferred. These (C) surfactants may be used alone or in combination of two or more.

[0092] From the viewpoint of dispersibility of the (B) melamine cyanurate, the content of the (C) surfactant is 0.01% by mass or more and 5.0% by mass or less, preferably 0.05% by mass or more and 3.0% by mass or less, and more preferably 0.1% by mass or more and 1.0% by mass or less, based on 100% by mass of the polyamide resin composition.

[0093] <Surface-modified (B) melamine cyanurate>

[0094] The polyamide resin composition can improve flame retardancy and toughness by dispersing (B) melamine cyanurate in (A) polyamide resin. As a method for dispersing (B) melamine cyanurate in (A) polyamide resin, for example, the following method can be cited: (B) melamine cyanurate is kneaded with (C) surfactant in advance, the (C) surfactant is spread evenly on the surface of (B) melamine cyanurate, and the surface-modified (B) melamine cyanurate obtained is used for extrusion processing with (A) polyamide resin.

[0095] Examples of a method for uniformly spreading the (C) surfactant on the surface of the (B) melamine cyanurate in advance include a method of mixing the two using a mixer such as a Henschel mixer or a planetary mixer.

[0096] By using the surface-modified (B) melamine cyanurate, (B) melamine cyanurate can be finely dispersed in the (A) polyamide resin.

[0097] When a thin film of a polyamide resin composition is photographed at a magnification of 100 times using a digital microscope, the total amount (number) of melamine cyanurate particles (B) in the image of 800 μm×800 μm square is set to 100%. 2 The ratio of the melamine cyanurate (B) in the form of the above particles is preferably less than 10%, more preferably less than 9%, and further preferably less than 5%. 2 When the ratio of the melamine cyanurate particles (B) is within the above range, there is a tendency to obtain a polyamide resin composition and a molded article thereof having good dispersibility of the melamine cyanurate (B), good flame retardancy and toughness.

[0098] In addition, the area of ​​10 μm 2 The ratio of the following (B) melamine cyanurate particles is preferably 10% or more and less than 50%, more preferably 15% or more and less than 45%, and further preferably 20% or more and less than 40%. 2 When the ratio of the following (B) melamine cyanurate particles is within the above range, there is a tendency to obtain a polyamide resin composition and a molded article thereof having good dispersibility of (B) melamine cyanurate and good flame retardancy and toughness.

[0099] Examples of methods for adjusting the ratio of the (B) melamine cyanurate particles include: surface modification of the (B) melamine cyanurate with the (C) surfactant, setting the screw speed relatively high when the polyamide resin composition is produced by melt kneading, adjusting the type of the (a-2) semi-aromatic polyamide, etc., to reduce the area by 100 μm. 2 The ratio of particles above 10μm 2The method of adjusting the ratio of the following particles, but not limited thereto. It should be noted that, when the screw speed is set to a relatively high speed, from the viewpoint of preventing the generation of discolored resin lumps called fouling, it is preferred to supply a portion of each of (a-1) aliphatic polyamide, (a-2) semi-aromatic polyamide and (C) surfactant from a relatively downstream supply port of the melt kneading device. The more fouling is generated (the longer the fouling is), the easier it is for the fouling to be mixed into the obtained polyamide resin composition particles. When the fouling is mixed, the appearance of the molded body obtained from the particles is easily damaged.

[0100] The ratio of the (B) melamine cyanurate particles can be specifically determined by the method described in the examples described below.

[0101] <Other ingredients>

[0102] To the polyamide resin composition of the present embodiment, various conventional elastomers, fillers, flame retardants, pigments or colorants such as titanium white and carbon black, metal hypophosphites such as sodium hypophosphite, heat stabilizers represented by hindered phenols, hindered amines, trialkyl phosphates and phosphites, lubricants such as higher fatty acid metal salts, higher fatty acid amides, higher fatty acid esters, various plasticizers, and various additives such as antistatic agents can be further added as needed within the range that does not impair the effects exerted by the polyamide resin composition of the present embodiment.

[0103] The water absorption of the polyamide resin composition of the present embodiment is preferably as small as possible. Specifically, the water absorption is preferably 5.5% or less, and more preferably 5.0% or less.

[0104] The water absorption rate of the polyamide resin composition refers to the mass change rate (%) after water absorption treatment measured by the method described in Examples described later.

[0105] The polyamide resin composition of the present embodiment preferably has a smaller value of the dimensional change rate upon water absorption. Specifically, the dimensional change rate upon water absorption is preferably 1.0% or less, and more preferably 0.6% or less.

[0106] The dimensional change rate of the polyamide resin composition upon water absorption refers to the dimensional change rate (%) in a specific direction after water absorption treatment measured by the method described in Examples described later.

[0107] The mechanical strength of the polyamide resin composition of the present embodiment can be evaluated by, for example, tensile strength and tensile breaking strain.

[0108] The polyamide resin composition of the present embodiment preferably has a larger value of tensile strength. Specifically, the tensile strength is preferably 60 MPa or more, and more preferably 70 MPa or more.

[0109] The polyamide resin composition of the present embodiment preferably has a larger tensile strain at break value. Specifically, the tensile strain at break is preferably 4.0% or more, and more preferably 6.0% or more.

[0110] In addition, the tensile strength and tensile breaking strain of the polyamide resin composition are values ​​measured according to ISO527, and can be measured specifically by the method described in the Examples described later.

[0111] The polyamide resin composition of the present embodiment preferably has a flame retardancy of V-0 at a thickness of 0.38 mm as measured by a UL-94 vertical burning test.

[0112] The polyamide resin composition of the present embodiment preferably has a flame retardancy of V-0 at a thickness of 0.75 mm as measured by a UL-94 vertical burning test.

[0113] In addition, the flame retardancy of the polyamide resin composition can be evaluated by the method described in the Examples mentioned later.

[0114] <Method for producing polyamide resin composition>

[0115] The method for producing the polyamide resin composition is not particularly limited. (A) polyamide resin, (B) melamine cyanurate, (C) surfactant, and other optional components may be melt-kneaded at once. However, from the viewpoint of the dispersibility of (B) melamine cyanurate, a part of (B) melamine cyanurate and all remaining components may be melt-kneaded, and then the remaining part of (B) melamine cyanurate may be added and further melt-kneaded. In addition, from the viewpoint of the dispersibility of (B) melamine cyanurate, as described above, (B) melamine cyanurate and (C) surfactant may be kneaded in advance to prepare (B) melamine cyanurate with surface modification, and then kneaded with (A) polyamide resin and other optional components.

[0116] The shape of the (A) polyamide resin is not particularly limited, but is preferably in the form of particles. In this case, from the viewpoint of simplifying the equipment, the (C) surfactant may be spread on the particle surface of the (A) polyamide resin, and then the (B) melamine cyanurate and any other components may be spread on the particle surface to prepare a blend, followed by melt kneading.

[0117] In the method for producing the polyamide resin composition, the method of melt kneading is not particularly limited, but preferably a method of using at least one raw material supply device to supply (A) polyamide resin, (B) melamine cyanurate, (C) surfactant and other optional components to an extruder for melt kneading. The components may be supplied to the extruder using different raw material supply devices, or only one raw material supply device may be used.

[0118] The extruder is not particularly limited, but a twin-screw extruder is preferred. Specific examples of the twin-screw extruder include ZSK series manufactured by Coperion, TEM series manufactured by Toshiba Machine Co., Ltd., and TEX series manufactured by The Nippon Steel Works, Ltd.

[0119] The L / D (screw effective length / screw outer diameter) of the twin-screw extruder is preferably 20 to 60, more preferably 30 to 50. In order to adjust the molecular weight of the (A) polyamide resin in the resin composition to a specific range, it is preferred to perform extrusion under the condition that the resin temperature when discharged from the nozzle at the front end of the extruder is 15° C. to 25° C. higher than the melting point of the polyamide as the main component, which can be controlled by the screw speed of the extruder and the number of kneading blocks (a block formed by a plurality of screw elements with a high kneading effect, called kneading disks) .

[0120] As a specific example, the barrel temperature of the twin-screw extruder is set to 230° C. to 280° C., and two kneading blocks are provided as the screw structure. In this case, it is preferred that the first kneading block is provided at the barrel at a position of about 40 / 100 to about 60 / 100 from the upstream of the twin-screw extruder, and the second kneading block is provided at the barrel at a position of about 70 / 100 to about 80 / 100 from the upstream of the twin-screw extruder.

[0121] There is no particular restriction on the method of supplying raw materials to the twin-screw extruder. There is no particular restriction on the raw material supply device, and a single-screw screw feeder, a twin-screw screw feeder, a flat feeder, a rotary feeder, a liquid supply pump, etc. can be used. Among them, from the aspect of less variation error in raw material supply, a weightless screw feeder is preferred. In addition, when multiple raw materials are added to one raw material supply device, at least two of the raw materials to be added can be mixed using a mixer, a conical mixer, etc. and then added.

[0122] <Molding>

[0123] The molded article of the present embodiment includes the flame-retardant polyamide resin composition of the present embodiment described above, and is obtained by molding the flame-retardant polyamide resin composition of the present embodiment described above.

[0124] The method for producing the molded body is not particularly limited, and a known molding method can be used. Examples of known molding methods include, but are not limited to, commonly known plastic molding methods such as press molding, injection molding, gas-assisted injection molding, welding molding, extrusion molding, blow molding, film molding, hollow molding, multilayer molding, and melt spinning.

[0125] The molded article of the present embodiment includes the polyamide resin composition of the present embodiment, and therefore has low water absorption, small rigidity change due to water absorption, small dimensional change rate during water absorption, and excellent flame retardancy and mechanical strength. Therefore, it can be suitably used as various parts such as automobile parts of electric vehicles, etc., which attach importance to mechanical properties, flame retardancy, and dimensional stability during water absorption, and electrical and electronic parts.

[0126] There are no particular limitations on automobile parts, and examples thereof include interior parts, exterior parts, electrical parts, intake system parts, cooling system parts, fuel system parts, etc. There are no particular limitations on electrical and electronic parts, and examples thereof include sockets, switches, housings, connectors, covers, etc.

[0127] Example

[0128] Hereinafter, the present embodiment will be described in more detail with reference to Examples and Comparative Examples, but the present embodiment is not limited to these Examples.

[0129] First, raw materials, measurement methods, and evaluation methods used in Examples and Comparative Examples are shown below.

[0130] <Raw Materials>

[0131] [(A) Polyamide resin]

[0132] [[(a-1) Aliphatic polyamide]]

[0133] · (a-1a): Polyamide 610

[0134] (Manufacturing method)

[0135] 1500 g of an equimolar salt of sebacic acid and hexamethylenediamine was mixed with 1500 g of distilled water to obtain a raw monomer aqueous solution. Next, the raw monomer aqueous solution was put into a 5-liter autoclave equipped with a stirring device and a discharge nozzle at the bottom, and the aqueous solution was fully stirred at a temperature of 50°C. Next, the autoclave was replaced with nitrogen five times, and then the temperature in the autoclave was raised from 50°C to about 270°C while stirring the aqueous solution. At this time, the pressure in the autoclave was about 1.8 MPa in terms of gauge pressure, and the water in the autoclave was discharged to the outside of the system at any time so that the pressure did not reach 1.8 MPa or more. In addition, the polymerization time was adjusted so that the sulfuric acid relative viscosity (ηr) of the polyamide resin reached the target value (2.50). After the polymerization in the autoclave was completed, the polyamide resin was sent out from the lower nozzle in the form of strands, and after water cooling and cutting, pellets of (a-1a) polyhexamethylene sebacamide (polyamide 610) were obtained. The polyamide 610 resin (a-1a) was vacuum dried at 80° C. for 24 hours. The sulfuric acid relative viscosity (ηr) of the polyamide 610 resin (a-1a) was measured as described below and was 2.3. In addition, Mw=30,000 and Mw / Mn=2.4.

[0136] (a-1b): Polyamide 612

[0137] (Manufacturing method)

[0138] 1500 g of an equimolar salt of dodecanedioic acid and hexamethylenediamine was dissolved in 1500 g of distilled water to prepare a 50% by mass uniform aqueous solution of the raw material monomers, which was placed in an autoclave with an internal volume of 5.4 L and purged with nitrogen.

[0139] While stirring at a temperature of 110°C to 150°C, water vapor was slowly extracted to concentrate the solution to a concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. This state was maintained for 1 hour until the internal temperature reached 245°C, and the reaction was continued for 1 hour while water vapor was slowly extracted and the pressure was maintained at 1.8 MPa.

[0140] Next, the pressure was reduced over 1 hour. Then, the autoclave was maintained at a reduced pressure of 650 Torr (86.66 kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C.

[0141] Then, the strands were pressurized with nitrogen and formed into strands from the lower spinneret (nozzle), water-cooled, cut, discharged in pellets, and dried at 100°C in a nitrogen atmosphere for 12 hours to obtain (a-1b) polyamide 612 resin with Mw=32000, Mw / Mn=2.4, and ηr=2.1.

[0142] (a-1c): Polyamide 66

[0143] (Manufacturing method)

[0144] 1500 g of an equimolar salt of adipic acid and hexamethylenediamine was dissolved in 1500 g of distilled water to prepare an equimolar 50% by mass uniform aqueous solution of the raw material monomers. The aqueous solution was placed in an autoclave with an internal volume of 5.4 L and purged with nitrogen.

[0145] While stirring at a temperature of 110°C to 150°C, water vapor was slowly extracted to concentrate the solution to a concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8 MPa. This state was maintained for 1 hour until the internal temperature reached 245°C, and the reaction was continued for 1 hour while water vapor was slowly extracted and the pressure was maintained at 1.8 MPa.

[0146] Next, the pressure was reduced over 1 hour. Then, the autoclave was maintained at a reduced pressure of 650 Torr (86.66 kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C.

[0147] Then, the strands were pressurized with nitrogen and formed into strands from the lower spinneret (nozzle), water-cooled, cut, discharged in pellets, and dried at 100° C. in a nitrogen atmosphere for 12 hours to obtain (a-1c) polyamide 66 resin with Mw=35000, Mw / Mn=2.0, and ηr=2.6.

[0148] [[(a-2) Semi-aromatic polyamide]]]

[0149] · (a-2a): Polyamide 6I

[0150] (Manufacturing method)

[0151] 1500g of an equimolar salt of isophthalic acid and hexamethylenediamine and 1.5 mol% excess of adipic acid relative to all equimolar salt components were dissolved in 1500g of distilled water to prepare an equimolar 50% uniform aqueous solution of the raw monomers. Then, water vapor was slowly extracted while stirring at a temperature of 110°C to 150°C and concentrated to a solution concentration of 70% by mass. Then, the internal temperature was raised to 220°C. At this time, the autoclave was pressurized to 1.8MPa. This state was maintained for 1 hour until the internal temperature reached 245°C, and the reaction was continued for 1 hour while slowly extracting water vapor and maintaining the pressure at 1.8MPa. Then, the pressure was reduced over 30 minutes. Next, the autoclave was maintained under a reduced pressure of 650 Torr (86.66kPa) for 10 minutes using a vacuum device. At this time, the final internal temperature of the polymerization was 265°C. Next, the strands were pressurized with nitrogen and formed into strands from the lower spinneret (nozzle), water-cooled, cut, discharged in pellets, and dried at 100° C. in a nitrogen atmosphere for 12 hours to obtain (a-2a) polyamide 6I resin.

[0152] The obtained polyamide 6I resin (a-2a) had Mw=20,000, Mw / Mn=2.0, ηr=1.63, and the content of the aromatic dicarboxylic acid unit in all the dicarboxylic acid units constituting the polyamide 6I resin (a-2a) was 100 mol %.

[0153] (a-2b): Polyamide 6I / 6T ("Grivory 21" manufactured by EMS Corporation, Mw = 27000, Mw / Mn = 2.2, ηr = 1.92)

[0154] [(B) Melamine cyanurate]

[0155] (b-1): melamine cyanurate, median particle size (D50): 10 μm, “MC-4500” manufactured by Nissan Chemical Co., Ltd.

[0156] [(C) Surfactant]

[0157] (c-1): Polyoxyethylene monolaurate, "EMANON (registered trademark) 1112 (PEM)" manufactured by Kao Corporation

[0158] (c-2): Polyethylene glycol, "PEG400 (PEG)" manufactured by Sanyo Chemical Co., Ltd.

[0159] <Measurement / Evaluation Methods of Physical Properties>

[0160] [Physical properties 1]

[0161] (Relative viscosity of sulfuric acid)

[0162] The 96% sulfuric acid relative viscosity ηr of the (A) polyamide resin was measured in accordance with JIS K6920.

[0163] [Physical Properties 2]

[0164] (Weight average molecular weight (Mw), number average molecular weight (Mn), molecular weight distribution (Mw / Mn))

[0165] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the (A) polyamide resin were determined by gel permeation chromatography (GPC). The device used was "HLC-8020" manufactured by Tosoh Corporation, the detector was a differential refractometer (RI), the solvent was hexafluoroisopropanol (HFIP), and the chromatographic columns used were 2 "TSKgel-GMHHR-H" and 1 "G1000 HHR" manufactured by Tosoh Corporation. The solvent flow rate was 0.6 mL / min, the sample concentration was 1 to 3 (mg sample) / 1 (mL solvent), and the insoluble components were removed by filtration using a filter to prepare a measurement sample. Based on the obtained elution curve, the ratio of the (A) polyamide resin and the weight average molecular weight (Mw) and number average molecular weight (Mn) were calculated by conversion to polymethyl methacrylate (PMMA), and the molecular weight distribution (Mw / Mn) was determined.

[0166] [Evaluation 1]

[0167] (Flame retardancy)

[0168] For each polyamide resin composition pellet, an injection molding machine ("PS40E" manufactured by Nissei Plastic Co., Ltd.) was used to set the molten resin temperature to 280°C and the mold temperature to 80°C to injection mold test pieces for UL-94 vertical burning test measurement (thickness: 0.38 mm, 0.75 mm). Using 5 test pieces of different thicknesses molded in this way, flame retardancy was evaluated based on the UL-94 vertical burning test, and judgments equivalent to flame retardancy V-0, V-1, V-2, and HB were implemented.

[0169] [Evaluation 2]

[0170] (Tensile strength, tensile breaking strain)

[0171] The pellets of each polyamide resin composition were molded into a multi-purpose test piece type A molded piece in accordance with ISO 3167 using an injection molding machine ("PS-40E" manufactured by Nissei Plastics Co., Ltd.) with the injection + holding time set to 25 seconds, the cooling time to 15 seconds, the mold temperature to 80° C., and the molten resin temperature to 270° C. Using the obtained molded piece, a tensile test was performed at a tensile speed of 50 mm / min in accordance with ISO 527, and the tensile strength (MPa) and tensile strain at break (%) were calculated.

[0172] [Evaluation 3]

[0173] (Water absorption)

[0174] For each polyamide resin composition pellet, an injection molding machine ("PS-40E" manufactured by Nissei Plastic Co., Ltd.) was used, and the injection + holding time was set to 25 seconds, the cooling time was 15 seconds, the mold temperature was 80°C, and the molten resin temperature was 270°C. ISO dumbbell-shaped specimens with a thickness of 4 mm were prepared and used as test pieces. The obtained ISO dumbbell-shaped specimens were immersed in pure water at a temperature of 23°C and subjected to a water absorption treatment for 1000 hours. The mass of the ISO dumbbell-shaped specimens before and after water absorption was measured, and the mass change rate before and after water absorption ((mass after water absorption - mass before water absorption) × 100 / mass before water absorption) was taken as the water absorption rate (%).

[0175] [Evaluation 4]

[0176] (Dimensional change rate when absorbing water)

[0177] For each polyamide resin composition pellet, an injection molding machine ("PS-40E" manufactured by Nissei Plastic Co., Ltd.) was used, with the injection + holding time set to 25 seconds, the cooling time to 15 seconds, the mold temperature to 80°C, and the molten resin temperature to 270°C, to mold a flat test piece of 80 mm (resin flow direction) × 60 mm × thickness 3 mm, and the initial size in the direction perpendicular to the resin flow direction was measured. Then, the pellet was immersed in pure water at a temperature of 23°C for 1000 hours of water absorption treatment, and then the size in the direction perpendicular to the resin flow direction was measured and used as the size when absorbing water. The value obtained by dividing the difference between the size when absorbing water and the initial size by the initial size is expressed as a percentage as the dimensional change rate (%) when absorbing water.

[0178] [Evaluation 5]

[0179] (Dispersibility of (B) Melamine Cyanurate in Polyamide Resin Composition)

[0180] For each polyamide resin composition, a slice with a thickness of 10 μm was prepared using a microtome. The slice was photographed at a magnification of 100 times using a digital microscope ("VHX-8000" manufactured by Keyence Corporation). For the (B) melamine cyanurate present in a square of 800 μm×800 μm, binarization processing was performed using python and image analysis was performed to calculate the area 100 μm when the total amount (number) of the (B) melamine cyanurate particles in the image was set to 100%. 2 The ratio (%) of the above (B) melamine cyanurate particles, area 10 μm 2 The following (B) is the ratio (%) of melamine cyanurate particles.

[0181] [Evaluation 6]

[0182] (Mold release)

[0183] For each polyamide resin composition pellet, an injection molding machine ("PS-40E" manufactured by Nissei Plastic Co., Ltd.) was used to prepare an ISO dumbbell-shaped specimen with a thickness of 4 mm, with the injection + holding time set to 25 seconds, the cooling time set to 15 seconds, the mold temperature set to 80°C, and the molten resin temperature set to 270°C. This was used as a test piece. At this time, the case where continuous molding was possible for 100 times was evaluated as "A (excellent)", the case where sticking to the mold occurred in 50 to 99 injections was evaluated as "B (poor)", and the case where sticking to the mold occurred in less than 50 injections was evaluated as "C (poor)", and the mold release property was evaluated.

[0184] [Evaluation 7]

[0185] (fouling)

[0186] For each polyamide resin composition, the length (mm) of the deposit attached to the outlet of the extruder tip nozzle 30 minutes after the start of production of the polyamide resin composition (start of polymer discharge from the extruder tip nozzle) was measured.

[0187] <Production of Polyamide Resin Composition>

[0188] [Example 1]

[0189] (Production of polyamide resin composition)

[0190] (a-1) polyamide 610, (a-2a) polyamide 6I, (b-1) melamine cyanurate, and (c-1) polyoxyethylene monolaurate were mixed in the ratio shown in Table 1 and fed to the first feed port of a twin-screw extruder ("ZSK-26Mc" manufactured by Coperion Corporation, barrel number 12) using a loss-in-weight feeder. Extrusion was performed under the conditions of a barrel temperature of 270°C, a discharge rate of 25 kg / hour, and a screw speed of 300 rpm.

[0191] The screw of the extruder is provided with two mixing blocks, wherein the first mixing block is provided at the fourth barrel of the extruder, and the second mixing block is provided at the eighth barrel of the extruder.

[0192] Next, the polymer was discharged from the nozzle at the front end of the extruder in the form of a strand, and after measuring the resin temperature, the strand was water-cooled and cut to obtain pellets of a polyamide resin composition.

[0193] [Example 2]

[0194] Pellets of a polyamide resin composition were obtained by the same method as in Example 1 except that (c-1) polyoxyethylene monolaurate was changed to (c-2) polyethylene glycol.

[0195] [Example 3]

[0196] 3000 g of (b-1) melamine cyanurate was added to a Henschel mixer FM20 (manufactured by Nippon Coke Industry Co., Ltd.), and 123 g of (c-1) polyoxyethylene monolaurate was added while stirring. The mixture was further stirred to obtain (b-1) melamine cyanurate with a surface treatment. Pellets of a polyamide resin composition were obtained by the same method as in Example 1, except that (b-1) melamine cyanurate with a surface treatment using (c-1) polyoxyethylene monolaurate was used instead of (b-1) melamine cyanurate and (c-1) polyoxyethylene monolaurate.

[0197] [Example 4]

[0198] Pellets of a polyamide resin composition were obtained by the same method as in Example 3 except that (c-1) polyoxyethylene monolaurate was changed to (c-2) polyethylene glycol.

[0199] [Example 5]

[0200] Pellets of a polyamide resin composition were obtained by the same method as in Example 1 except that the mixing ratio of (a-1a) polyamide 610 and (a-2a) polyamide 6I was changed.

[0201] [Example 6, Example 7]

[0202] In Examples 6 and 7, pellets of a polyamide resin composition were obtained by the same methods as in Examples 1 and 3, respectively, except that the (a-1a) polyamide 610 was changed to the (a-1b) polyamide 612.

[0203] [Example 8, Example 9]

[0204] In Examples 8 and 9, pellets of a polyamide resin composition were obtained by the same methods as in Examples 1 and 3, respectively, except that (a-1a) polyamide 610 was changed to (a-1c) polyamide 66.

[0205] [Example 10]

[0206] Pellets of a polyamide resin composition were obtained by the same method as in Example 1 except that (a-2a) polyamide 6I was changed to (a-2b) polyamide 6I / 6T.

[0207] [Example 11]

[0208] Pellets of a polyamide resin composition were obtained by the same method as in Example 1 except that the blending ratio of (c-1) polyoxyethylene monolaurate was changed.

[0209] [Example 12]

[0210] Pellets of a polyamide resin composition were obtained by the same method as in Example 1 except that the blending ratio of (b-1) melamine cyanurate was changed.

[0211] [Example 13]

[0212] Pellets of a polyamide resin composition were obtained by the same method as in Example 3 except that the blending ratio of (a-1a) polyamide 610 and (a-2a) polyamide 6I was changed.

[0213] [Example 14]

[0214] (a-1) polyamide 610, (a-2a) polyamide 6I, (b-1) melamine cyanurate, and (c-1) polyoxyethylene monolaurate were mixed in the ratio shown in Table 1 and supplied to the first supply port and the second supply port of a twin-screw extruder ("ZSK-26Mc" manufactured by Coperion Corporation, barrel number 12) using a loss-in-weight feeder. Extrusion was performed under the conditions of a barrel temperature of 270°C, a discharge rate of 25 kg / hour, and a screw speed of 500 rpm.

[0215] The screw of the extruder is provided with two kneading blocks. The first kneading block is provided at the fourth barrel of the extruder, and the second kneading block is provided at the eighth barrel of the extruder. The second supply port is provided at the fifth barrel of the extruder, and (a-1) polyamide 610, (a-2a) polyamide 6I, and (c-1) polyoxyethylene monolaurate are introduced from the side.

[0216] Next, the polymer was discharged from the nozzle at the front end of the extruder in the form of a strand, and after measuring the resin temperature, the strand was water-cooled and cut to obtain pellets of a polyamide resin composition.

[0217] [Example 15]

[0218] Pellets of a polyamide resin composition were obtained in the same manner as in Example 1 except that the screw rotation speed of the extruder was adjusted to 500 rpm.

[0219] [Comparative Examples 1 to 12]

[0220] The composition of each component was adjusted to the composition described in Table 1, and pellets of each polyamide resin composition were produced.

[0221] In Comparative Examples 2, 8 and 12, similarly to Example 3, pellets of a polyamide resin composition were obtained by using (b-1) melamine cyanurate surface-treated with (c-1) polyoxyethylene monolaurate instead of (b-1) melamine cyanurate and (c-1) polyoxyethylene monolaurate.

[0222] The physical properties of the polyamide resin compositions obtained were measured by the above-mentioned methods, and various evaluations were performed. The results are shown in Table 1.

[0223] [Table 1-1]

[0224]

[0225] [Table 1-2]

[0226]

[0227] Industrial Applicability

[0228] The polyamide resin composition of the present invention and the molded product obtained by molding the polyamide resin composition have low water absorption, small dimensional change rate when absorbing water, excellent flame retardancy and mechanical strength. Therefore, the molded product of the present invention can be suitably used as various parts such as automobile parts and electric and electronic parts.

Claims

1. A flame retardant polyamide resin composition comprising (A) a polyamide resin, (B) melamine cyanurate and (C) a surfactant, wherein the (A) polyamide resin comprises (a-1) an aliphatic polyamide and (a-2) a semi-aromatic polyamide, wherein: When the flame-retardant polyamide resin composition is set to 100 mass %, the flame-retardant polyamide resin composition includes: 55 mass % to 95 mass % of the (a-1) aliphatic polyamide, 1 mass % to 30 mass % of the (a-2) semi-aromatic polyamide, 4 mass % to 15 mass % of the (B) melamine cyanurate, and 0.01 mass % to 5.0 mass % of the (C) surfactant.

2. The flame retardant polyamide resin composition according to claim 1, wherein When the sheet of the flame-retardant polyamide resin composition is photographed at a magnification of 100 times using a digital microscope, the total amount (number) of the (B) melamine cyanurate particles in the 800 μm×800 μm square image is set to 100%, and the area of ​​100 μm in the 800 μm×800 μm square image is calculated. 2 The ratio of the (B) melamine cyanurate in the form of the above particles is less than 10%.

3. The flame retardant polyamide resin composition according to claim 1 or 2, wherein When the sheet of the flame-retardant polyamide resin composition is photographed at a magnification of 100 times using a digital microscope, the total amount (number) of the (B) melamine cyanurate particles in the 800 μm×800 μm square image is set to 100%, and the area of ​​10 μm in the 800 μm×800 μm square image is calculated. 2 The ratio of the (B) melamine cyanurate in the form of particles is 10% or more and less than 50%.

4. The flame retardant polyamide resin composition according to claim 1 or 2, wherein The (B) melamine cyanurate is melamine cyanurate surface-modified by the (C) surfactant.

5. A molded body, characterized in that: The molded article is obtained by molding the flame-retardant polyamide resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Flame-retardant polyamide rein composition

    JP2000026721A

  • Flame-retardant polyamide resin composition and process for producing the same

    JP2008007614A

  • Polyamide resin composition and molding thereof

    JP2018070808A